Improvement of Onboarding Period: Development of the Onboarding Period at OMRON Healthcare Europe Following the Pilot Implementation of the Intranet Page and Tool - Shirley Waskito (iBuss Management, 2022)
One of the biggest challenges for a company is retaining employee, companies would like employees to stay in the company long term as high employee turnover is not only very expensive but also impacts the productivity of the company. There are many factors that impacts the employee turnover rate of a company, one of the main factors is onboarding. It is crucial that the onboarding period of a new hire is successful to ensure that they would stay in the company long-term. OMRON Healthcare Europe is the industry leader for healthcare products specifically blood pressure monitors and nebulizers. This paper aims to provide insight to the current onboarding period at OMRON Healthcare Europe and provide recommendation on how to improve it further following the implementation of the intranet page and tool. A case study was conducted in OMRON Healthcare Europe by identifying the elements that a successful onboarding period should have, analysing and evaluating the current onboarding period as well conducting a preliminary evaluation on the new features that has recently been added into the onboarding period. Surveys was distributed and interviews were conducted to gain information. Secondary research using journals, websites and internal Share point as well as social media as its sources were conducted as well. The researcher proposes new structure as well as new features to be added to the onboarding period at OMRON Healthcare Europe.Keywords: Onboarding, Human Resources Management, Project implementation, Employee turnover